2016
DOI: 10.1556/2006.5.2016.035
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology of Online Poker Players: Review of Literature

Abstract: Background and aimsOnline Texas Hold’em poker has become a spectacular form of entertainment in our society, and the number of people who use this form of gambling is increasing. It seems that online poker activity challenges existing theoretical concepts about problem gambling behaviors. The purpose of this literature review is to provide a current overview about the population of online poker players.MethodsTo be selected, articles had to focus on psychopathology in a sample of online poker players, be writt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 49 publications
(132 reference statements)
2
43
0
Order By: Relevance
“…The first limit of the study is linked to the population (Moreau, Chabrol, & Chauchard, 2016). The online recruitment of gamblers made it difficult to reach individuals who gamble regularly on games that are principally practiced off-line (e.g.…”
Section: Limits Of the Studymentioning
confidence: 99%
“…The first limit of the study is linked to the population (Moreau, Chabrol, & Chauchard, 2016). The online recruitment of gamblers made it difficult to reach individuals who gamble regularly on games that are principally practiced off-line (e.g.…”
Section: Limits Of the Studymentioning
confidence: 99%
“…Poker is a card game which was created in the United States in the 1820s (Moreau & Chabrol, 2016) and is the most popular card game in the world (Loon, Assem, & Dolder, 2015). In short words, this is a game where from two to 10 players are dealt cards, and where they bet on who has 'the best hand'.…”
Section: Poker Game Vs Investmentmentioning
confidence: 99%
“…The skill element and the way the betting is organized together make it possible for some players to win in the long run unlike most forms of gambling (Bjerg, 2010;Laakasuo, Palomäki, & Salmela, 2015;McCormack & Griffiths, 2011). This is one of the main motivations for the players, but to develop these skills in poker requires substantial invested time than any other form of gambling (Laakasuo et al, 2015;Moreau, Chabrol, & Chauchard, 2016;Recher & Griffiths, 2012). As a result several studies have showed that poker may produce a new type of problem gambler, one who does not struggle financially, but instead spend so much time on poker that other parts of their life is affected, such as work, their relationships with others, and their education (Barrault, Untas, & Varescon, 2014;Biolcati et al, 2015;Bjerg, 2010;Griffiths, Parke, Wood, & Rigbye, 2010;Hing, Holdsworth, Tiyce, & Breen, 2014;Hing, Russell, Blaszczynski, & Gainsbury, 2015;Hopley & Nicki, 2010;Laakasuo et al, 2015;Shead, Hodgins, & Scharf, 2008).…”
Section: Poker Is Highly Time Consumingmentioning
confidence: 99%
“…Treatment centers in Denmark report an increase of young poker players in need of treatment from virtually no patients in 2003 to 33% of their patients in 2009 (Bjerg, 2010). In a French survey 20% of the patients in a gambling treatment center were poker players, including 75% of the online players (Venisse & Grall-Bronnec, as cited in Moreau et al, 2016).…”
Section: Poker Is Highly Time Consumingmentioning
confidence: 99%